Co-occurrence of stunting and off-track early child development in low- and middle-income countries - Jeong, Joshua; Chi, Hyejun; Bliznashka, Lilia; Pitchik, Helen O.; Kim, Rockli (American Medical Association, 2025)
Importance: Although children across low- and middle-income countries (LMICs) are increasingly surviving, many are not fully thriving. Both stunting and off-track early child development (ECD) hinder children’s potential to thrive.